2007
DOI: 10.1111/j.1559-1816.2007.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Use of Environmentally Friendly Modes of Transportation Caused by Perceived Mobility Necessities: An Extension of the Theory of Planned Behavior1

Abstract: An extended version of the theory of planned behavior (TPB; Ajzen, 1991) was used to explain travel mode choice. As a new predictor, perceived mobility necessities (PMNs) were introduced, which are defined as people's perceptions of mobility‐related consequences of their personal living circumstances. The database consisted of a survey of 1,545 car users in 3 large German cities. Using structural equation modeling, PMNs were integrated into TPB and showed the expected significant negative effect on use of envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 20 publications
3
117
1
Order By: Relevance
“…It is, in turn, acclaimed for its great success and remarkable predictive power in empirical studies [77] or profoundly criticised and utterly disregarded [78]. Through years of widespread applications in many fields, it has been modified and many variations exist in literature; researchers have added more variables to try to more accurately predict future behaviour: anticipated emotions [79], perceived mobility needs [80], personal norms [34]. Furthermore, Conner and Armitage [81] proposed to add six variables to the initial model: (1) belief salience; (2) locus of control, that builds up the perceived behavioural control together with self-efficacy; (3) moral norms; (4) self-identity, that expresses the recognition of the potential and qualities of the individual to cover his/her societal role; (5) affective beliefs, anticipated emotions or regret; (6) past behaviour/habit.…”
Section: Individual-focused Theories Of Decision-makingmentioning
confidence: 99%
“…It is, in turn, acclaimed for its great success and remarkable predictive power in empirical studies [77] or profoundly criticised and utterly disregarded [78]. Through years of widespread applications in many fields, it has been modified and many variations exist in literature; researchers have added more variables to try to more accurately predict future behaviour: anticipated emotions [79], perceived mobility needs [80], personal norms [34]. Furthermore, Conner and Armitage [81] proposed to add six variables to the initial model: (1) belief salience; (2) locus of control, that builds up the perceived behavioural control together with self-efficacy; (3) moral norms; (4) self-identity, that expresses the recognition of the potential and qualities of the individual to cover his/her societal role; (5) affective beliefs, anticipated emotions or regret; (6) past behaviour/habit.…”
Section: Individual-focused Theories Of Decision-makingmentioning
confidence: 99%
“…The factors in both studies were mainly derived from the Theory of Planned Behaviour (Ajzen, 1991) and included social norm, perceived behavioural control, and attitudes in relation to functional and symbolic aspects of different transport modes. In addition, perceived mobility necessities (PMN; Haustein & Hunecke, 2007) were added accounting for effects of the actual living situation on modal choices and activity frequency. In both studies, factors were selected for segmentation when they showed a significant effect on at least two different aspects of mobility behaviour: mode choice, activity frequency, or distances travelled.…”
Section: Attitudinal Factorsmentioning
confidence: 99%
“…Due to a variety of reasons ranging from the intrinsic appeal of automobiles, urban sprawl, increasing demands of the labor market with regard to employees' flexibility and mobility, increasing female participation in labor, to a decline in traditional household structures, the previous century is characterized by an extraordinary growth in car use that has continued into the current century (Haustein and Hunecke 2007). As a result, in today's society, cars play a dominant role in the travel behavior of people, causing serious environmental (e.g.…”
Section: Introductionmentioning
confidence: 99%